2021
DOI: 10.1016/j.clnu.2021.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Deep neural network for automatic volumetric segmentation of whole-body CT images for body composition assessment

Abstract: Background & aims: Body composition analysis on CT images is a valuable tool for sarcopenia assessment. We aimed to develop and validate a deep neural network applicable to whole-body CT images of PET-CT scan for the automatic volumetric segmentation of body composition. Methods: For model development, one hundred whole-body or torso 18 F-fluorodeoxyglucose PETeCT scans of 100 patients were retrospectively included. Two radiologists semi-automatically labeled the following seven body components in every CT ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 43 publications
(49 reference statements)
0
91
0
Order By: Relevance
“…Abdominal CT images were uploaded to commercially available deep learning-based software for body composition analysis (DeepCatch R v1.0.0.0; Medicalip Co. Ltd., Seoul). This software package provides automatic volumetric segmentation of the following seven body components with an accuracy of 97% [ 30 ]: skin, muscle, abdominal visceral fat, subcutaneous fat, bone, internal organs and vessels, and the central nervous system. In addition, the software provides automatic localization of the third lumbar vertebral body (L3), and automatically quantifies L3 sectional area (cm 2 ) and mean CT attenuations (Hounsfield Units, HU) of visceral abdominal fat, subcutaneous abdominal fat, and abdominal muscle components ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Abdominal CT images were uploaded to commercially available deep learning-based software for body composition analysis (DeepCatch R v1.0.0.0; Medicalip Co. Ltd., Seoul). This software package provides automatic volumetric segmentation of the following seven body components with an accuracy of 97% [ 30 ]: skin, muscle, abdominal visceral fat, subcutaneous fat, bone, internal organs and vessels, and the central nervous system. In addition, the software provides automatic localization of the third lumbar vertebral body (L3), and automatically quantifies L3 sectional area (cm 2 ) and mean CT attenuations (Hounsfield Units, HU) of visceral abdominal fat, subcutaneous abdominal fat, and abdominal muscle components ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, we used this deep neural network-based software for automatic volumetric segmentation of body composition (skeletal muscle, abdominal visceral fat, and subcutaneous fat) from anonymized, precontrast CT images in DICOM format. According to the previous validation study, the software's average segmentation accuracy was reported as 97% compared with manual segmentation (21). After segmentation, the abdominal waist was automatically labeled based on WHO's waist definition (29): between the lower end of the thoracic ribs and the upper end of the iliac crest.…”
Section: Imaging Analysismentioning
confidence: 99%
“…Researchers have measured individuals' area of skeletal muscle and adipose tissue at the third lumbar vertebral body (L3)-level cross-sectional image of CT scans, which is known to reflect amounts of total body muscle and adipose tissue well (19,20). In addition, the latest high-throughput technology allows automated and fast volumetric measurements of each component from CT scans (21,22). With the use of such an advanced tool, tracking the volumetric change of specific body composition components is feasible (23), which has not yet been investigated in early cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To determine sarcopenia, these studies commonly measured skeletal muscle area from a single computed tomography (CT) scan image, based on previous findings that the third lumbar vertebra (L3)-level cross-sectional image reflects total body muscle mass and adipose tissues well [ 15 , 16 ]. Beyond the areal measurement, recent technological advances enable the volumetric measurement of a specific body composition component, such as skeletal muscle, visceral fat, and subcutaneous fat, from the CT scans that were not feasible due to the requirement of substantial time and human effort [ 17 ]. The volumetric measurement of body composition may contain more abundant and precise information than areal measurements in a single cross-sectional image [ 18 ].…”
Section: Introductionmentioning
confidence: 99%